Digital Preservation through Interface Design: A Semiotic Analysis in File Saving Systems - Martins, Alan David Bitencourt; Mota, Marcelle Pereira (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: Digital preservation research seeks strategies to ensure the longevity and accessibility of digital information, mitigating risks of obsolescence and the loss of cultural, historical, and scientific heritage. Interface design plays a crucial role in shaping user behavior and influencing digital preservation practices. Problem: Widely used systems, such as word processors and operating systems, often lack explicit digital preservation strategies. The absence of features like metadata completion, open format adoption, and automated backups creates a gap between system capabilities and sustainable preservation practices, limiting users’ ability to ensure long-term access to their data. Solution: This research applies the Semiotic Inspection Method (MIS) to critically analyze the messages conveyed by save file interfaces in Microsoft Word and Windows 10. The study identifies gaps and opportunities to integrate design guidelines that encourage digital preservation, focusing on sustainable formats, metadata management, and user awareness. IS Theory: Grounded in Semiotic Engineering, the research interprets user-system interaction as a communicative process. By reconstructing designers’ meta-messages, it evaluates how interface design supports—or hinders—digital preservation. Method: The study employs a qualitative, exploratory approach using the Semiotic Inspection Method to analyze static, dynamic, and metalinguistic signs in Microsoft Word and Windows 10 interfaces. This method reconstructs implicit designer messages to assess their alignment with digital preservation needs. Results: The analysis reveals that current interfaces prioritize efficiency and usability but neglect explicit communication of digital preservation strategies. Users receive no direct encouragement to adopt open formats, complete metadata, or implement backup routines. The findings emphasize the need for educational and interactive features that guide users toward sustainable digital preservation practices. Contributions and Impact in the IS Field: This study contributes to Information Systems (IS) research by proposing interface design guidelines that align usability with digital preservation principles, enhancing informational sustainability. Academically, it expands the application of MIS to evaluate system design in the context of digital preservation.